Comparison of SYNTAX Score And Residual SYNTAX Score in Patients Undergoing Multivessel Coronary Intervention - Mumtaz, Zahid; Aslam Khattak, Zahoor; Bilal Siddique, Muhammad; Ali Rizvi, Syed Murtaza; Bilal, Ahmed; Ishaq, Zeeshan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To associate the SYNTAX score, residual SYNTAX score and in-hospital outcomes in patients who underwent multivessel Percutaneous Coronary Intervention. Study Design: Analytical, Cross-sectional Study. Place and Duration of Study: Cardiac Cath Lab, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, Pakistan, from Jul to Oct 2023. Methodology: Total three hundred and sixty-six patients who underwent multivessel coronary intervention were included using non-probability consecutive sampling. Patients with history of CABG and complex coronary artery disease were excluded. SYNTAX score and residual SYNTAX score were calculated. Chi-square test and Wilcoxon Signed Rank test were applied to find associations. p<0.05 was considered as statistically significant. Results: In a study of 366 participants, 292(79.8%) were males and 74(20.2%) were females whose mean age was 62.01±8.67 years, 136(37.2%) had diabetes, 177(48.4%) were hypertensive, and 153(41.8%) were smokers. NSTEMI was present in 173(47.2%) patients, and 43(11.7%) had LMS disease. In-hospital outcomes included 5(1.4%) repeat revascularization cases, 3(0.8%) Myocardial Infarction cases and 2(0.5%) death cases. SYNTAX Score had insignificant association with mortality (p=0.05), while residual SYNTAX score was significantly associated with repeat revascularization, MI, and mortality (p<0.01). Pre and post-procedural SYNTAX score were also different significantly (p<0.001). Conclusion: Our study underscored the predictive importance of SYNTAX Score and residual SYNTAX Score in guiding optimal treatment decisions for improved outcomes in multivessel coronary intervention.